Detached-eddy and large-eddy simulations of wind effects on a high-rise structure. (3rd June 2017) - Yan, B.W.; Li, Q.S.
Highlights: Carry out a combined wind tunnel test and CFD study on the wind effects on an elliptical cylinder. Investigate the surface roughness effects on the wind loading of an elliptical cylinder using DES. DES and LES models and numerical treatments adopted in this study can provide reasonably good correspondence with wind tunnel tests. DES model can reproduce the effects of surface roughness effects on the wind loading with the modified wall function. Abstract: In this study, detached-eddy simulations (DES) and large-eddy simulations (LES) of wind effect on a high-rise structure with elliptical shape are performed. The aim of this study is to examine the accuracy of the numerical simulations for wind flow around a complex high-rise structure and investigate the effects of surface roughness on the wind loading. In order to reproduce appropriate inflow turbulence, the improved recycling method combined with the weighted amplitude wave superposition (WAWS) method is used to generate the inflow turbulence in the streamwise direction. Also, to study the surface roughness effects on the wind loading, the rough wall boundary conditions are adopted in the DES models. Typical results including the mean and fluctuating pressure coefficients, force spectra, Reynolds stresses and wind-induced top-floor response are obtained and compared with the corresponding wind tunnel experimental data. Through the cross-comparisons, the numerical results by the DES and LES models are found to be comparable with the experimental results. Additionally, the surface roughness effects on the wind loading is well reproduced with the DES models, such as the slow pressure recovery in the separation regions and the increased mean drag force coefficients. It is demonstrated through the validations that the DES and LES models and the numerical treatments adopted in this study can provide reasonably good results.